Polyurethane modified epoxy high-damping sound-absorbing material and preparation method thereof
Patent Information
- Application Number
- CN202611180047.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-27
AI Technical Summary
如专利CN104845045A公开了聚氨酯改性环氧高阻尼材料,通过胺类固化体系提升基体韧性,但该技术存在明显缺陷:最终材料阻尼峰值低(tanδ<0.7)、有效阻尼温域狭窄(宽度<30℃),阻尼稳定性与工况适配性较差,且无法同步兼顾阻尼与吸声性能
1. 本申请通过精准分子结构调控设计,实现吸声材料高阻尼宽温域特性。即聚氨酯改性环氧树脂采用三段梯度升温反应,将体系NCO含量控制在3.8%~3.9%窄区间,有效规整树脂微相分离结构,硬段微区尺寸均匀分布,有效解决传统改性树脂结构无序、阻尼稳定性差的问题。本申请吸声材料阻尼峰值提升至0.80以上,有效阻尼温域拓宽至45℃以上,与未改性环氧基吸声材料相比,阻尼峰值提升3倍以上,取得了预料不到的技术效果,为声能耗散提供稳定的分子本征基础。
Smart Images

Figure CN122978685A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the technical field of polymer functional damping sound-absorbing materials, and particularly relates to a polyurethane modified epoxy high damping sound-absorbing material and its preparation method. Background Technology
[0002] Polymer sound-absorbing materials can convert incident sound energy into heat energy dissipation through mechanisms such as structural deformation, interfacial friction, and microporous resonance, making them core functional materials in the field of vibration reduction and noise reduction. Epoxy resin has advantages such as high mechanical strength, good adhesion, simple molding process, and excellent weather resistance, making it a commonly used matrix for composite sound-absorbing materials. However, conventional bisphenol A type epoxy resin has a high crosslinking density and strong molecular chain rigidity, exists in a glassy state at room temperature, has a low damping loss factor (tanδ < 0.3), and weak sound energy dissipation ability, making it difficult to meet the engineering requirements of mid-to-high frequency broadband sound absorption and high-damping vibration reduction.
[0003] To improve the damping performance of epoxy resin, existing technologies generally employ polyurethane modification. For example, patent CN104845045A discloses a polyurethane-modified epoxy high-damping material, which improves the toughness of the matrix through an amine curing system. However, this technology has significant drawbacks: the final material has a low peak damping (tanδ < 0.7), a narrow effective damping temperature range (width < 30℃), poor damping stability and adaptability to operating conditions, and cannot simultaneously achieve both damping and sound absorption performance.
[0004] Patent CN114806376A discloses a vibration reduction and noise reduction material for ships, which adopts a two-layer composite structure of a polyurethane urea damping layer and an epoxy resin restraining layer. Its limitations are: the layer coating process is complex, and there is a risk of insufficient adhesion between layers and easy delamination and peeling, which limits the application of thick sizes; the function focuses on damping of low-frequency vibrations from 1 to 1000 Hz, and the absorption performance of mid-to-high frequency sound waves above 5 kHz is insufficient, which makes it difficult to meet the needs of underwater acoustic stealth and mid-to-high frequency industrial noise reduction; the single-component damping layer has low mechanical strength and needs to rely on the restraining layer for reinforcement, and it is impossible to achieve the organic unity of high damping, high sound absorption and good mechanical properties with a single material.
[0005] Hollow glass microspheres, with their low density, high porosity, and closed microporous structure, are widely used in the preparation of lightweight sound-absorbing composite materials. Patents CN101719367A and CN120775477A disclose technical solutions for multi-size hollow microspheres combined with mica powder to modify epoxy materials, aiming to improve the sound absorption performance of the materials. However, the applicant has discovered a long-standing inherent technical bias in this field: existing technologies typically employ a preparation method of uniformly blending all fillers, generally believing that optimizing the filler particle size distribution and achieving uniform dispersion is sufficient to obtain superior sound absorption effects. The resulting homogeneous porous structure suffers from poor acoustic impedance matching and high sound wave reflectivity, making it difficult to improve the material's sound absorption performance.
[0006] Carbon nanotubes, as one-dimensional nanomaterials, possess characteristics such as large specific surface area, high interfacial friction coefficient, and excellent mechanical properties. Currently, carbon nanotubes are primarily used for material mechanical enhancement and dimensional stability optimization; however, their role in nanofacial damping and energy dissipation has not been fully explored and utilized.
[0007] In summary, existing sound-absorbing materials suffer from poor damping performance, low sound absorption efficiency, simple structural design, and inability to achieve multiple performance characteristics simultaneously. Furthermore, polyurethane modification, hollow microsphere porous modification, and carbon nanotube reinforcement technologies are all independent applications that can only address localized issues such as matrix damping, structural sound absorption, and mechanical reinforcement. Summary of the Invention
[0008] To address at least one of the aforementioned technical problems, this application aims to develop a sound-absorbing material that combines high damping and high sound absorption, with a damping peak value ≥0.80, an effective damping temperature range ≥45℃, an average sound absorption coefficient ≥0.78, a peak sound absorption coefficient ≥0.88, and a minimum reflection coefficient ≤0.11, while also possessing the advantages of being lightweight, high-strength, and having stable performance. This application provides a polyurethane-modified epoxy high-damping sound-absorbing material and its preparation method.
[0009] This application provides a polyurethane-modified epoxy high-damping sound-absorbing material, which is prepared by mixing and curing component A and component B at a mass ratio of 100:(31~34). The mass proportions of each raw material component in component A include: 100 parts of polyurethane-modified epoxy resin, 0.8~1.2 parts of coupling agent, 8~12 parts of liquid polysulfide rubber, 5~7 parts of hollow glass microspheres NH3O, 5~7 parts of hollow glass microspheres NH14O, 3.5~4.0 parts of wet-process flake mica, 0.5~0.7 parts of carbon nanotubes, and 0.8~1.2 parts of fumed silica. The mass proportions of each raw material component in component B include: 34~37 parts of polyetheramine, 0.2 parts of coupling agent, 1.0~1.2 parts of accelerator, and hollow glass microspheres NH10O. 4-5 parts, and 0.4 parts of fumed silica; wherein the hollow glass microspheres have a D50 particle size of 90 μm for NH10, a D50 particle size of 45 μm for NH30, and a D50 particle size of 20 μm for NH140.
[0010] Optionally, the mass ratio of each raw material component in the preparation of the polyurethane modified epoxy resin includes: 78-82 parts of polypropylene glycol, 14.5-15.5 parts of toluene diisocyanate, 90-95 parts of epoxy resin, and 28-40 parts of epoxy reactive diluent.
[0011] Further optionally, the preparation of the polyurethane-modified epoxy resin includes the following steps: Sa, Polypropylene glycol was dehydrated at 100℃ under vacuum for more than 2 hours to remove free water from the system. After cooling to 38℃, toluene diisocyanate was added. The reaction was terminated immediately when the NCO mass fraction of the system was 3.8%~3.9% to obtain NCO-terminated polyurethane prepolymer. Sb. Add pre-dehydrated epoxy resin and epoxy reactive diluent to the NCO-terminated polyurethane prepolymer obtained in step Sa, mix well, and heat to 110℃ for constant temperature reaction. When the NCO mass fraction of the system is ≤0.5%, cool down and discharge the material to obtain polyurethane modified epoxy resin.
[0012] Further optionally, in step Sa, the reaction between polypropylene glycol and toluene diisocyanate adopts a three-stage gradient heating reaction, the specific process of which is as follows: holding at 60℃ for 30 min to complete the initial addition, holding at 80℃ for 30 min to regularize the molecular chain, and reacting at 100℃ until the mass fraction of NCO in the system is 3.8%~3.9%.
[0013] Further optionally, the polypropylene glycol is selected from PPG2000, the toluene diisocyanate is selected from TDI-80, and the epoxy resin is selected from E44 epoxy resin.
[0014] Optionally, in component A, the coupling agent is selected from silane coupling agent KH-560, and the liquid polysulfide rubber is selected from liquid polysulfide rubber LP-3.
[0015] Optionally, in component B, the polyetheramine is selected as polyetheramine D400, the coupling agent is selected as silane coupling agent KH-550, and the accelerator is selected as DMP-30.
[0016] Optionally, the fumed silica in both component A and component B is hydrophobic fumed silica.
[0017] On the other hand, this application also provides a method for preparing the above-mentioned polyurethane-modified epoxy high-damping sound-absorbing material, including the following steps: S1. Preparation of polyurethane-modified epoxy resin; S2. Preparation of Component A: According to the formula amount, polyurethane modified epoxy resin, coupling agent, carbon nanotubes and fumed silica are mixed and dispersed at high speed of 1200~1500 r / min for 30 min. The speed is then reduced to 300~400 r / min, liquid polysulfide rubber, hollow glass microspheres NH30, hollow glass microspheres NH140 and wet-process flaky mica are added and dispersed at low speed for 30 min to obtain Component A. S3. Preparation of component B: According to the formula amount, mix polyetheramine, coupling agent, accelerator, hollow glass microspheres NH10 and fumed silica, stir evenly and then obtain component B. S4. Preparation of polyurethane-modified epoxy high-damping sound-absorbing material: Mix component A and component B in proportion, degas under vacuum, cast into shape, pre-cur at room temperature for 24 hours, and then cure at 60℃ for 4 days to obtain polyurethane-modified epoxy high-damping sound-absorbing material.
[0018] Optionally, in step S4, the conditions for vacuum degassing are: vacuum degree ≤ -0.09MPa, and degassing time is 3~5min.
[0019] In summary, the present invention has at least one of the following beneficial technical effects: 1. This application achieves high-damping, wide-temperature-range characteristics in sound-absorbing materials through precise molecular structure control design. Specifically, the polyurethane-modified epoxy resin undergoes a three-stage gradient heating reaction, controlling the NCO content within a narrow range of 3.8%–3.9%. This effectively regulates the resin's microphase separation structure, resulting in a uniform distribution of hard segment micro-region sizes, effectively solving the problems of disordered structure and poor damping stability inherent in traditional modified resins. The sound-absorbing material of this application exhibits a peak damping value exceeding 0.80 and an effective damping temperature range exceeding 45℃. Compared to unmodified epoxy-based sound-absorbing materials, the peak damping value is increased by more than three times, achieving unexpected technical results and providing a stable intrinsic molecular basis for sound energy dissipation.
[0020] 2. This application breaks through industry technical biases by constructing a gradient impedance structure in situ. It abandons the industry-standard all-filler blending process and pioneers a technology that adds hollow glass microspheres of different particle sizes separately in groups. Utilizing the coupling effect of curing agent penetration and dynamic changes in system viscosity, a continuous impedance gradient structure is generated in situ in one step. This structure enables precise matching of the acoustic impedance of the sound-absorbing material with different media such as air and water, significantly reducing the surface reflectivity of sound waves and increasing the proportion of effective incident sound energy. Under the premise of identical filler types and total dosage, the average sound absorption coefficient of the sound-absorbing material in this application is increased by 15%–22% compared to traditional homogeneous structures, and the minimum reflection coefficient is reduced by 56%–76%.
[0021] 3. This application develops a novel nano-damping mechanism using carbon nanotubes to achieve multi-scale synergistic energy dissipation. It overcomes the limitations of using carbon nanotubes for single-scale mechanical enhancement by utilizing their ultra-high specific surface area to construct numerous nano-interfaces within the resin. Under the influence of acoustic waves, high-frequency interfacial slippage and friction are generated, adding a new dimension of refined acoustic energy dissipation at the nanoscale. Combining intrinsic resin damping at the molecular scale, micron-scale microbead and micropore resonance with mica sheet friction, and macro-scale gradient impedance matching, a four-level synergistic energy dissipation system is constructed, with performance far exceeding the combined effect of single modification methods.
[0022] 4. This application features synergistic process optimization, balancing structural integrity and performance stability. A differentiated step-by-step process of "high-speed dispersion of nanofillers followed by low-speed dispersion of microfillers" is employed. This not only solves the carbon nanotube agglomeration problem but also effectively protects the closed microporous structure of the hollow glass microspheres, ensuring a stable closed-pore ratio of ≥95%. This process guarantees the stability and consistency of the material's damping and sound absorption performance.
[0023] 5. The sound-absorbing material of this application exhibits balanced overall performance and strong engineering adaptability. Specifically, the sound-absorbing material obtained in this application combines high sound absorption, high damping, lightweight, and high strength characteristics, with an average sound absorption coefficient ≥0.78, a peak sound absorption coefficient ≥0.88, a minimum reflection coefficient ≤0.11, a compressive strength ≥3.45MPa, a Shore D hardness ≥52, and a density ≤0.92g / cm³. 3 It can be adapted to complex working conditions in multiple scenarios, and has extremely high engineering application value. Attached Figure Description
[0024] Figure 1 Comparison curves of DMA damping performance of sound-absorbing materials in the examples and comparative examples; Figure 2 Comparison curves of sound absorption / reflection performance of sound-absorbing materials in the examples and comparative examples. Detailed Implementation
[0025] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.
[0026] This application provides a polyurethane-modified epoxy high-damping sound-absorbing material, which is prepared by mixing and curing component A and component B at a mass ratio of 100:(31~34). The mass proportions of each raw material component in component A include: 100 parts of polyurethane-modified epoxy resin, 0.8~1.2 parts of coupling agent, 8~12 parts of liquid polysulfide rubber, 5~7 parts of hollow glass microspheres NH3O, 5~7 parts of hollow glass microspheres NH14O, 3.5~4.0 parts of wet-process flake mica, 0.5~0.7 parts of carbon nanotubes, and 0.8~1.2 parts of fumed silica. The mass proportions of each raw material component in component B include: 34~37 parts of polyetheramine, 0.2 parts of coupling agent, 1.0~1.2 parts of accelerator, and hollow glass microspheres NH10O. 4-5 parts, and 0.4 parts of fumed silica; wherein the hollow glass microspheres have a D50 particle size of 90 μm for NH10, a D50 particle size of 45 μm for NH30, and a D50 particle size of 20 μm for NH140.
[0027] The preparation method of the above-mentioned polyurethane modified epoxy high-damping sound-absorbing material of this application includes the following steps: S1. Preparation of polyurethane-modified epoxy resin; S2. Preparation of Component A: According to the formula amount, polyurethane modified epoxy resin, coupling agent, carbon nanotubes and fumed silica are mixed and dispersed at high speed of 1200~1500 r / min for 30 min. The speed is then reduced to 300~400 r / min, liquid polysulfide rubber, hollow glass microspheres NH30, hollow glass microspheres NH140 and wet-process flaky mica are added and dispersed at low speed for 30 min to obtain Component A. S3. Preparation of component B: According to the formula amount, mix polyetheramine, coupling agent, accelerator, hollow glass microspheres NH10 and fumed silica, stir evenly and then obtain component B. S4. Preparation of polyurethane-modified epoxy high-damping sound-absorbing material: Mix component A and component B in proportion, degas under vacuum, cast into shape, pre-cur at room temperature for 24 hours, and then cure at 60℃ for 4 days to obtain polyurethane-modified epoxy high-damping sound-absorbing material.
[0028] Through extensive research and experimentation, the applicant discovered that existing polyurethane-modified epoxy materials suffer from low damping peak values, narrow effective damping temperature ranges, poor damping stability and adaptability to operating conditions, and an inability to simultaneously achieve both damping and sound absorption performance. This is primarily due to the lack of precise NCO content control in the preparation of the polyurethane prepolymer, poor controllability of the reaction process, and a wide molecular weight distribution in the prepolymer, leading to disordered microphase separation in the modified resin. Furthermore, the filler system has not been optimized for sound absorption scenarios. Additionally, prior to this application, existing technologies for multi-size hollow microspheres combined with mica powder-modified epoxy materials, due to the uniform blending of all fillers, can only form a homogeneous porous structure. This fails to construct an impedance gradient along the material's thickness, resulting in poor acoustic impedance matching between the material and air or water media, high surface reflectivity, low proportion of incident effective sound energy, and a significant bottleneck in the overall sound absorption performance, making it difficult to overcome the performance limitations of homogeneous structures.
[0029] Based on the aforementioned new technological challenges, the applicant overcame technological biases and designed the solution presented in this application, effectively addressing the problems of low damping, narrow temperature range, high sound wave reflectivity, and limited sound absorption efficiency in traditional sound-absorbing materials. This application breaks through industry technological biases by adopting a synergistic coupling approach involving polyurethane molecular modification, carbon nanotube nano-interface modification, and gradient micron-sized porous structures. It achieves this by precisely controlling the segmented synthesis of high-damping polyurethane-modified epoxy resin using NCO, combined with differentiated particle size hollow glass microspheres in grouped blends and carbon nanotube nano-interface modification. This constructs a four-scale (molecular-nano-micro-macro) synergistic damping sound absorption system, encompassing molecular-scale intrinsic resin damping, nanoscale carbon nanotube interfacial friction, micron-scale hollow glass microsphere micropore resonance and mica sheet slip, and macro-scale gradient impedance matching. This system achieves a synergistic upgrade in material damping, sound absorption, lightweight, and mechanical properties. In particular, this application abandons the industry-standard uniform blending process for all fillers and pioneers a technical solution for the independent / differentiated addition of hollow glass microspheres of different particle sizes: During the mixing and curing process of components A and B, the hollow glass microspheres NH10 diffuse into component A along with the polyetheramine curing agent, and are fixed in situ due to the increasing viscosity of the system, forming a gradient impedance structure with dense small-diameter microspheres on the surface and increasing large-diameter microspheres inside along the thickness direction of the sound-absorbing material. In addition, this application adopts a differentiated step-by-step process of "first dispersing nanofillers at high speed, then dispersing micron fillers at low speed", which effectively overcomes the defects of traditional dispersion processes, such as carbon nanotube agglomeration and hollow microsphere breakage, which lead to modification failure and destruction of the integrity of the porous structure.
[0030] The sound-absorbing material of this application is suitable for various application scenarios, including underwater acoustic concealment, noise reduction of industrial equipment, vibration reduction of rail transit, and acoustic noise reduction of buildings.
[0031] The following are preparation examples and embodiments of this application.
[0032] The main raw materials used in the preparation examples and embodiments of this application are all commercially available.
[0033] Among them, hollow glass microspheres are products of Shanxi Hainuo Technology Co., Ltd.: the D50 particle size of NH10 is about 90μm, the D50 particle size of NH30 is about 45μm, and the D50 particle size of NH140 is about 20μm; wet-process flaky mica AT-100M is a product of Lingshou Antai Mining Co., Ltd., with a particle size of 100 mesh; carbon nanotube powder NTP3023 is a product of Shenzhen Nanoport Co., Ltd.; fumed silica HB-139C is a product of Hubei Huifu Nanomaterials Co., Ltd.; liquid polysulfide rubber LP-3 is a product of Toray Fine Chemicals Co., Ltd. of Japan, with Mn=1000; polyetheramine D400 is a product of Huntsman Advanced Materials (Shanghai) Co., Ltd., with an amine value of 260-290 mg KOH / g, Mn=400; Accelerator DMP-30 is a product of Changzhou Shanfeng Chemical Co., Ltd., with a purity ≥95%; Toluene diisocyanate TDI-80 is a product of Wanhua Chemical Group Co., Ltd., with NCO%=48.2%; Polypropylene glycol PPG2000 is a product of Shandong Lanxing Dongda Co., Ltd., with a hydroxyl value of 56 mg KOH / g and Mn=2000; E44 epoxy resin is a product of Baling Petrochemical Co., Ltd., with an epoxy value of 0.44 mol / 100g; 622 epoxy reactive diluent is a product of Hubei Green Home Materials Technology Co., Ltd., with an epoxy value of 0.74-0.84 mol / 100g; Methyltetrahydrophthalic anhydride is a product of Puyang Huicheng Electronic Materials Co., Ltd., with an anhydride content ≥41%; silane coupling agents KH560 and KH550 are products of Nanjing Shuguang Chemical Group Co., Ltd., with a purity ≥98%.
[0034] The following is a preparation example of this application.
[0035] The polyurethane-modified epoxy resin prepared in this application is synthesized via the following route:
[0036] Specifically, it is prepared using the following two-step method (prepolymer preparation and graft modification), including the following steps: Sa, Polypropylene glycol PPG2000 was dehydrated at 100℃ under vacuum for more than 2 hours to remove free water from the system. After cooling to 38℃, toluene diisocyanate TDI-80 was added. A three-stage gradient temperature increase reaction was adopted: initial addition was completed at 60℃ for 30 minutes, molecular chain regularization was completed at 80℃ for 30 minutes, and the reaction was carried out at 100℃. The NCO mass fraction of the system was monitored in real time. When the NCO content reached 3.8%~3.9%, the reaction was terminated immediately to obtain a polyurethane prepolymer with narrow molecular weight distribution and uniform hardness structure. Sb. Add pre-dehydrated E44 epoxy resin and 622 epoxy reactive diluent to the NCO-terminated polyurethane prepolymer obtained in step Sa. After mixing, heat to 110℃ and react at a constant temperature. Continuously monitor the NCO content. When the NCO mass fraction of the system is ≤0.5%, cool down and discharge the material to obtain polyurethane modified epoxy resin.
[0037] Preparation Example 1 The mass ratio of each raw material component of the polyurethane modified epoxy resin in this embodiment includes: 78 parts of polypropylene glycol PPG2000, 15.5 parts of toluene diisocyanate TDI-80, 90 parts of E44 epoxy resin, and 28 parts of 622 epoxy reactive diluent.
[0038] Preparation Example 2 The mass ratio of each raw material component in the polyurethane modified epoxy resin of this embodiment includes: 82 parts of polypropylene glycol PPG2000, 14.5 parts of toluene diisocyanate TDI-80, 95 parts of E44 epoxy resin, and 40 parts of 622 epoxy reactive diluent.
[0039] Preparation Example 3 The mass ratio of each raw material component in the polyurethane modified epoxy resin of this embodiment includes: 80 parts of polypropylene glycol PPG2000, 15 parts of toluene diisocyanate TDI-80, 92.5 parts of E44 epoxy resin, and 34 parts of 622 epoxy reactive diluent.
[0040] The following are embodiments of this application.
[0041] The polyurethane-modified epoxy high-damping sound-absorbing material of this application embodiment is prepared by the following method, including the following steps: S1. Select a specific polyurethane-modified epoxy resin; S2. Preparation of Component A: According to the formulation, polyurethane modified epoxy resin, silane coupling agent KH-560, carbon nanotubes NTP3023 and fumed silica HB-139C are mixed and dispersed at high speed at 1350 r / min for 30 min (to achieve complete deagglomeration and uniform dispersion of carbon nanotubes, and at the same time to build a stable thixotropic system). The speed is reduced to 350 r / min, and liquid polysulfide rubber LP-3, hollow glass microspheres NH30, hollow glass microspheres NH140 and wet-process flake mica AT-100M are added and dispersed at low speed for 30 min (to avoid the breakage of hollow glass microspheres caused by high-speed shear and ensure that the closed-cell rate of the material is ≥95%) to obtain Component A. S3. Preparation of component B: According to the formula amount, mix polyetheramine D400, silane coupling agent KH-550, accelerator DMP-30, hollow glass microspheres NH10 and fumed silica HB-139C, and stir evenly at low speed to obtain component B. S4. Curing and molding: Mix components A and B in proportion, degas for 5 minutes under vacuum of -0.09MPa, remove air bubbles from the system, and then cast into shape. First, pre-cur at room temperature for 24 hours to set the shape, and then cure at 60℃ for 4 days to complete the overall curing. During the curing process, a thickness gradient impedance sound absorption structure is formed in situ, thus obtaining polyurethane modified epoxy high damping sound absorption material.
[0042] In step S3, under the catalysis of accelerator DMP-30, the thiol groups and epoxy groups at both ends of the liquid polysulfide rubber LP-3 undergo ring-opening addition reactions, participating in the construction of the curing crosslinking network and introducing flexible polysulfide segments, which can further improve the damping loss and interfacial toughness of the sound-absorbing material. During the curing process of component A and component B, the large-diameter hollow glass microspheres NH10 in component B slowly penetrate and diffuse into the matrix of component A along with the polyetheramine D400 curing agent. As the curing reaction progresses, the viscosity of the system continues to increase, and the diffusion movement of the microspheres is gradually restricted and fixed in situ. Finally, a continuous impedance gradient structure of "dense small-diameter microspheres on the surface and gradually increasing large-diameter microspheres in the interior" is spontaneously formed in the thickness direction of the sound-absorbing material. No secondary processing is required, the process is simple and the structure is controllable.
[0043] Example 1 The polyurethane-modified epoxy high-damping sound-absorbing material of this embodiment is prepared by compounding and curing component A and component B in a mass ratio of 100:32.
[0044] The mass proportions of each raw material component in component A include: 100 parts of polyurethane modified epoxy resin, 1.0 part of silane coupling agent KH-560, 10 parts of liquid polysulfide rubber LP-3, 6 parts of hollow glass microspheres NH30, 6 parts of hollow glass microspheres NH140, 3.5 parts of wet-process flaky mica AT-100M, 0.6 parts of carbon nanotubes NTP3023, and 1.0 part of fumed silica HB-139C.
[0045] The mass proportions of each raw material component in component B include: 35 parts of polyetheramine D400, 0.2 parts of silane coupling agent KH-550, 1.0 part of accelerator DMP-30, 4 parts of hollow glass microspheres NH10, and 0.4 parts of fumed silica HB-139C.
[0046] In this embodiment, the polyurethane-modified epoxy resin of Preparation Example 1 was selected.
[0047] Example 2 The polyurethane-modified epoxy high-damping sound-absorbing material of this embodiment is prepared by compounding and curing component A and component B in a mass ratio of 100:34.
[0048] The mass proportions of each raw material component in component A include: 100 parts polyurethane modified epoxy resin, 0.8 parts silane coupling agent KH-560, 8 parts liquid polysulfide rubber LP-3, 5 parts hollow glass microspheres NH30, 5 parts hollow glass microspheres NH140, 3.5 parts wet-process flaky mica AT-100M, 0.5 parts carbon nanotubes NTP3023, and 0.8 parts fumed silica HB-139C.
[0049] The mass proportions of each raw material component in component B include: 37 parts of polyetheramine D400, 0.2 parts of silane coupling agent KH-550, 1.0 part of accelerator DMP-30, 4 parts of hollow glass microspheres NH10, and 0.4 parts of fumed silica HB-139C.
[0050] In this embodiment, the polyurethane-modified epoxy resin prepared in Example 2 was selected.
[0051] Example 3 The polyurethane-modified epoxy high-damping sound-absorbing material of this embodiment is prepared by compounding and curing component A and component B in a mass ratio of 100:31.
[0052] The mass proportions of each raw material component in component A include: 100 parts polyurethane modified epoxy resin, 1.2 parts silane coupling agent KH-560, 12 parts liquid polysulfide rubber LP-3, 7 parts hollow glass microspheres NH30, 7 parts hollow glass microspheres NH140, 4 parts wet-process flaky mica AT-100M, 0.7 parts carbon nanotubes NTP3023, and 1.2 parts fumed silica HB-139C.
[0053] The mass proportions of each raw material component in component B include: 34 parts of polyetheramine D400, 0.2 parts of silane coupling agent KH-550, 1.2 parts of accelerator DMP-30, 5 parts of hollow glass microspheres NH10, and 0.4 parts of fumed silica HB-139C.
[0054] In this embodiment, the polyurethane-modified epoxy resin of Preparation Example 3 was selected.
[0055] Example 4 The polyurethane-modified epoxy high-damping sound-absorbing material of this embodiment is prepared by compounding and curing component A and component B in a mass ratio of 100:34.
[0056] The mass proportions of each raw material component in component A include: 100 parts of polyurethane modified epoxy resin, 1.0 part of silane coupling agent KH-560, 8 parts of liquid polysulfide rubber LP-3, 6 parts of hollow glass microspheres NH30, 6 parts of hollow glass microspheres NH140, 3.5 parts of wet-process flaky mica AT-100M, 0.6 parts of carbon nanotubes NTP3023, and 1.0 part of fumed silica HB-139C.
[0057] The mass proportions of each raw material component in component B include: 37 parts of polyetheramine D400, 0.2 parts of silane coupling agent KH-550, 1.0 part of accelerator DMP-30, 4 parts of hollow glass microspheres NH10, and 0.4 parts of fumed silica HB-139C.
[0058] In this embodiment, the polyurethane-modified epoxy resin of Preparation Example 3 was selected.
[0059] Example 5 The polyurethane-modified epoxy high-damping sound-absorbing material of this embodiment is prepared by compounding and curing component A and component B in a mass ratio of 100:34.
[0060] The mass proportions of each raw material component in component A include: 100 parts of polyurethane modified epoxy resin, 1.0 part of silane coupling agent KH-560, 8 parts of liquid polysulfide rubber LP-3, 6.5 parts of hollow glass microspheres NH30, 6.5 parts of hollow glass microspheres NH140, 3.5 parts of wet-process flaky mica AT-100M, 0.6 parts of carbon nanotubes NTP3023, and 1.0 part of fumed silica HB-139C.
[0061] The mass proportions of each raw material component in component B include: 37 parts of polyetheramine D400, 0.2 parts of silane coupling agent KH-550, 1.0 part of accelerator DMP-30, 4 parts of hollow glass microspheres NH10, and 0.4 parts of fumed silica HB-139C.
[0062] In this embodiment, the polyurethane-modified epoxy resin of Preparation Example 3 was selected.
[0063] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that component A uses E44 epoxy resin instead of polyurethane-modified epoxy resin and liquid polysulfide rubber LP-3; component B uses methyltetrahydrophthalic anhydride instead of polyetheramine D400 and silane coupling agent KH-550. This is to verify the effect of polyurethane-modified epoxy resin on improving the damping of sound-absorbing materials.
[0064] The sound-absorbing material in this comparative example was prepared by compounding and curing components A and B in a mass ratio of 100:72.
[0065] The mass proportions of each raw material component in component A include: 100 parts of E44 epoxy resin, 1.0 part of silane coupling agent KH-560, 6 parts of hollow glass microspheres NH30, 6 parts of hollow glass microspheres NH140, 3.5 parts of wet-process flaky mica AT-100M, 0.6 parts of carbon nanotubes NTP3023, and 1.0 part of fumed silica HB-139C.
[0066] The mass proportions of each raw material component in component B include: 80 parts of methyltetrahydrophthalic anhydride, 1.0 part of accelerator DMP-30, 4 parts of hollow glass microspheres NH10, and 0.4 parts of fumed silica HB-139C.
[0067] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses a polyurethane-modified epoxy resin + liquid polysulfide rubber + carbon nanotube system, without adding hollow glass microspheres and wet-processed sheet mica. This is to verify the sound absorption gain effect of the micron-sized porous filler.
[0068] The sound-absorbing material in this comparative example was prepared by compounding and curing components A and B in a mass ratio of 100:33.
[0069] The mass proportions of each raw material component in component A include: 100 parts of polyurethane modified epoxy resin, 1.0 part of silane coupling agent KH-560, 10 parts of liquid polysulfide rubber LP-3, 0.6 parts of carbon nanotubes NTP3023, and 1.0 part of fumed silica HB-139C.
[0070] The mass proportions of each raw material component in component B include: 35 parts of polyetheramine D400, 0.2 parts of silane coupling agent KH-550, 1.0 part of accelerator DMP-30, and 0.4 parts of fumed silica HB-139C.
[0071] This comparative example uses the polyurethane-modified epoxy resin prepared in Example 1.
[0072] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that hollow glass microspheres and wet-processed flake mica were all uniformly blended and added to component A using a traditional homogenization process without a gradient impedance structure. This was to verify the technical gain effect of the gradient structure.
[0073] The sound-absorbing material in this comparative example was prepared by compounding and curing components A and B in a mass ratio of 100:28.
[0074] The mass proportions of each raw material component in component A include: 100 parts of polyurethane modified epoxy resin, 1.0 part of silane coupling agent KH-560, 10 parts of liquid polysulfide rubber LP-3, 4 parts of hollow glass microspheres NH10, 6 parts of hollow glass microspheres NH30, 6 parts of hollow glass microspheres NH140, 3.5 parts of wet-process flaky mica AT-100M, 0.6 parts of carbon nanotubes NTP3023, and 1.0 part of fumed silica HB-139C.
[0075] The mass proportions of each raw material component in component B include: 35 parts of polyetheramine D400, 0.2 parts of silane coupling agent KH-550, 1.0 part of accelerator DMP-30, and 0.4 parts of fumed silica HB-139C.
[0076] This comparative example uses the polyurethane-modified epoxy resin prepared in Example 1.
[0077] The performance of the sound-absorbing materials in Examples 1-5 and Comparative Examples 1-3 was tested. The test results are shown in Table 1 below. Figures 1-2 As shown.
[0078] Among them, the glass transition temperature (Tg) and the loss factor tanδ peak value were tested according to the tensile mode in GB / T 33061.1-2025 "Determination of Dynamic Mechanical Properties of Plastics". The sample size was 25mm×6mm×3mm, the heating rate was 3℃ / min, the test frequency was 1Hz, and the test temperature range was -40℃~100℃. The temperature corresponding to the peak value of the tanδ curve was taken as the glass transition temperature Tg (e.g., ...). Figure 1 ).
[0079] Average absorption coefficient, peak absorption coefficient, and minimum reflection coefficient: Tested according to the underwater acoustic tube method in GB / T 14369-2011 "Methods for Measurement of Insertion Loss, Echo Reduction and Absorption Coefficient of Acoustic Materials". The sample is cylindrical, 56mm in diameter and 30mm thick. The test frequency range is 5kHz~23kHz. Calculate the average absorption coefficient, peak absorption coefficient, and minimum reflection coefficient (e.g., ...) within this frequency band. Figure 2 ).
[0080] Density: Tested according to the immersion method described in GB / T 1033.1-2008 "Determination of density of non-foamed plastics - Part 1: Immersion method, liquid specific gravity bottle method and titration method", with a sample mass ≥1g and a test environment temperature of 23℃.
[0081] Shore D hardness: Tested according to the method described in GB / T 2411-2008 "Determination of indentation hardness (Shore hardness) of plastics and hard rubber using a hardness tester". The total thickness of the sample is ≥6mm (multiple layers are stacked if the thickness is insufficient). The distance between the test point and the edge of the sample is ≥12mm. The average value of 5 test points is taken.
[0082] Compressive strength: Tested according to the method described in GB / T 1041-2008 "Determination of compressive properties of plastics". The sample is cylindrical with a diameter of 20 mm and a height of 20 mm. The compression rate is 5 mm / min. The compressive strength value at 10% strain is taken.
[0083] Closed-cell rate: Tested according to GB / T 10799-2008 "Determination of open-cell and closed-cell volume percentage of rigid foamed plastics" using the gas displacement method (AccuPyc II 1340 true density meter), with each sample tested 3 times and the average value taken.
[0084] Table 1. Detection results of Examples 1-5 and Comparative Examples 1-3 ; A comparison of the data from Examples 1-5 and Comparative Example 1 in Table 1 shows that the damping peak value of Examples 1-5 in this application is increased by more than 3 times, and the average sound absorption coefficient is increased by more than 1 time. This demonstrates that the specific polyurethane-modified epoxy resin used in this application is the core foundation for the high damping and high sound absorption of the sound-absorbing material.
[0085] By comparing the data from Examples 1-5 with those from Comparative Example 2 in Table 1, it can be seen that the average sound absorption coefficient of Examples 1-5 of this application is increased by 24%-32%, and the minimum reflection coefficient is significantly reduced. This demonstrates that the gradient porous structure of the sound-absorbing material of this application has a core sound-absorbing effect.
[0086] The data in Table 1, comparing the data of Example 1 and Comparative Example 3, shows that Example 1 of this application has an average sound absorption coefficient that is 20.6% higher and a minimum reflection coefficient that is 72.0% lower. It is evident that the sound-absorbing material prepared by this application using a specific method of distributing hollow glass microspheres and wet-process flake mica, along with the process, exhibits significantly better performance than sound-absorbing materials prepared through conventional formula optimization and traditional processes, which is not readily apparent.
[0087] From the data in Table 1 and Figures 1-2 As can be seen, the technical solutions of embodiments 1-5 of this application, which utilize multi-scale synergistic enhancement and group-differentiated construction of gradient impedance structures, achieve balanced optimization of sound-absorbing material damping, sound absorption, lightweight, and mechanical strength, and the overall performance is significantly better than that of comparative examples 1-3. In addition, the effective damping temperature range of the sound-absorbing materials in embodiments 1-5 of this application is broadened to above 45℃ (tanδ>0.3).
[0088] Any part not described in detail in this specification belongs to the prior art.
[0089] The above are all preferred embodiments of this application, and are not intended to limit the scope of protection of this application. Therefore, all equivalent changes made in accordance with the structure, shape and principle of this application should be covered within the scope of protection of this application.
Claims
1. A polyurethane-modified epoxy high-damping sound-absorbing material, characterized in that, The mixture is prepared by mixing and curing components A and B at a mass ratio of 100:(31~34). The mass proportions of components A include: 100 parts polyurethane-modified epoxy resin, 0.8~1.2 parts coupling agent, 8~12 parts liquid polysulfide rubber, 5~7 parts hollow glass microspheres NH3O, 5~7 parts hollow glass microspheres NH14O, 3.5~4.0 parts wet-process flaky mica, 0.5~0.7 parts carbon nanotubes, and 0.8~1.2 parts fumed silica. The mass proportions of components B include: 34~37 parts polyetheramine, 0.2 parts coupling agent, 1.0~1.2 parts accelerator, and hollow glass microspheres NH10O. 4-5 parts, and 0.4 parts of fumed silica; wherein the hollow glass microspheres have a D50 particle size of 90 μm for NH10, a D50 particle size of 45 μm for NH30, and a D50 particle size of 20 μm for NH140.
2. The polyurethane-modified epoxy high-damping sound-absorbing material according to claim 1, characterized in that, The mass ratio of each raw material component in the preparation of the polyurethane modified epoxy resin includes: 78-82 parts of polypropylene glycol, 14.5-15.5 parts of toluene diisocyanate, 90-95 parts of epoxy resin, and 28-40 parts of epoxy reactive diluent.
3. The polyurethane-modified epoxy high-damping sound-absorbing material according to claim 2, characterized in that, The preparation of the polyurethane-modified epoxy resin includes the following steps: Sa, Polypropylene glycol was dehydrated at 100℃ under vacuum for more than 2 hours to remove free water from the system. After cooling to 38℃, toluene diisocyanate was added. The reaction was terminated immediately when the NCO mass fraction of the system was 3.8%~3.9% to obtain NCO-terminated polyurethane prepolymer. Sb. Add pre-dehydrated epoxy resin and epoxy reactive diluent to the NCO-terminated polyurethane prepolymer obtained in step Sa, mix well, and then heat to 110℃ for constant temperature reaction. When the NCO mass fraction of the system is ≤0.5%, cool down and discharge the material to obtain polyurethane modified epoxy resin.
4. The polyurethane-modified epoxy high-damping sound-absorbing material according to claim 3, characterized in that, In step Sa, the reaction between polypropylene glycol and toluene diisocyanate adopts a three-stage gradient heating reaction, the specific process of which is as follows: initial addition is completed by holding at 60℃ for 30 min, molecular chain regularization is completed by holding at 80℃ for 30 min, and reaction is carried out at 100℃ until the mass fraction of NCO in the system is 3.8%~3.9%.
5. The polyurethane-modified epoxy high-damping sound-absorbing material according to claim 3, characterized in that, The polypropylene glycol is selected from PPG2000, the toluene diisocyanate is selected from TDI-80, and the epoxy resin is selected from E44 epoxy resin.
6. The polyurethane-modified epoxy high-damping sound-absorbing material according to claim 1, characterized in that, In component A, the coupling agent is silane coupling agent KH-560, and the liquid polysulfide rubber is liquid polysulfide rubber LP-3.
7. The polyurethane-modified epoxy high-damping sound-absorbing material according to claim 1, characterized in that, In component B, the polyetheramine is selected as polyetheramine D400, the coupling agent is selected as silane coupling agent KH-550, and the accelerator is selected as DMP-30.
8. The polyurethane-modified epoxy high-damping sound-absorbing material according to claim 1, characterized in that, The fumed silica in both component A and component B is hydrophobic fumed silica.
9. A method for preparing a polyurethane-modified epoxy high-damping sound-absorbing material according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1. Preparation of polyurethane-modified epoxy resin; S2. Preparation of Component A: According to the formula amount, polyurethane modified epoxy resin, coupling agent, carbon nanotubes and fumed silica are mixed and dispersed at high speed of 1200~1500 r / min for 30 min. The speed is then reduced to 300~400 r / min, liquid polysulfide rubber, hollow glass microspheres NH30, hollow glass microspheres NH140 and wet-process flaky mica are added and dispersed at low speed for 30 min to obtain Component A. S3. Preparation of component B: According to the formula amount, mix polyetheramine, coupling agent, accelerator, hollow glass microspheres NH10 and fumed silica, stir evenly and then obtain component B. S4. Preparation of polyurethane-modified epoxy high-damping sound-absorbing material: Mix component A and component B in proportion, degas under vacuum, cast into shape, pre-cur at room temperature for 24 hours, and then cure at 60℃ for 4 days to obtain polyurethane-modified epoxy high-damping sound-absorbing material.
10. The method for preparing the polyurethane-modified epoxy high-damping sound-absorbing material according to claim 9, characterized in that, In step S4, the conditions for vacuum degassing are: vacuum degree ≤ -0.09MPa, and degassing time is 3~5min.
Citation Information
Patent Citations
Low-density underwater sound absorbing plate and preparation method thereof
CN101719367A
Room-temperature curable epoxy resin based high damping material and preparation method thereof
CN104845045A
Sound absorption and insulation coating as well as preparation method and application thereof
CN120775477A